Stress Distribution of Endodontically Treated Tooth MOD Cavity Restored with Ribbon Fiber-Reinforced Composite (Wallpapering Technique) Using Finite Element Method - Rahmayanti ZA; Aripin D; Muryani A; Yolanda Y; Dharsono HDA; Mihradi S; Wicaksono S (Dove Medical Press, 2024)
Zenita Aisah Rahmayanti,1 Dudi Aripin,1 Anna Muryani,1 Yolanda Yolanda,1 Hendra Dian Adhita Dharsono,1 Sandro Mihradi,2 Satrio Wicaksono2 1Department of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Faculty of Mechanical and Aerospace Engineering, Bandung Institute of Technology, Bandung, IndonesiaCorrespondence: Anna Muryani, Department of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Jl. Sekeloa Selatan no. 1, Bandung, 40123, Indonesia, Tel +62 896 19972132, Email anna.muryani@unpad.ac.idPurpose: This research aimed to describe the stress distribution of an endodontically treated tooth with a mesio-occluso-distal (MOD) cavity restored with direct composite reinforced with polyethylene and e-glass ribbon fiber.Methods: This research was a descriptive study using the finite element method. A 3D model of the mandibular first molar solid after endodontic treatment with class II MOD preparation was prepared using Solidworks software. Finite element simulation was carried out using Abaqus software. In the first simulation, 180 N force was applied (vertically 90° perpendicular to the occlusal surface) at four points of loading: the tip of the mesiobuccal and distobuccal cusp, central fossa, and distal marginal ridge. For the second simulation, a 100 N force was applied at a 45° lateral angle to the occlusal surface at two loading points: the lingual slope of the mesiobuccal and distobuccal cusp.Results: This study showed that the stress concentration was located in the occlusal pit and fissure, CEJ distal area, bifurcation in dentin, and the 1/3 cervical area of root dentin. The stress value generated after vertical and lateral force did not exceed the tooth and restoration's compressive and tensile strength value. The failure occurred at the interface of enamel and composite near the loading point area due to vertical load, both on polyethylene and e-glass fiber ribbon-reinforced composite restoration. Stress distribution of an endodontically treated tooth with a MOD cavity restored with ribbon fiber-reinforced composite using the finite element method showed that the highest stress concentration occurred on the surface close to the loading point, in narrow, concave, and sharp areas, and more apically for endodontically treated teeth.Conclusion: Neither the tooth nor restoration failed after vertical and horizontal loads. The interface between enamel and composite on the occlusal surface failed.Keywords: direct composite restoration, fiber-reinforced composite, wallpapering technique, finite element